Coherent Anti-Stokes Raman Scattering Spectroscopy Using a Double-Wavelength-Emission Electronically Tuned Ti:Sapphire Laser. Issue 8 (August 2021) - Hirai, Nao; Maeda, Yasuhiro; Hashimoto, Kosuke; Andriana, Bibin B.; Matsuyoshi, Hiroko; Sato, Hidetoshi
Coherent anti-Stokes Raman scattering (CARS) spectroscopy is a powerful tool for Raman imaging technology. In contrast, conventional spontaneous Raman spectroscopy is often used for biological analysis with multivariate analysis. This study develops a new type of CARS instrument with a double-wavelength-emission, background-free, electronically tuned Ti:sapphire laser (DW-ETL). DW-ETL generates two laser pulses with different wavelengths simultaneously within its single resonator. The pulse wavelength and buildup time are regulated by acousto-optical tunable filter in the resonator. The present DW-ETL CARS system is free from any mechanical movement to measure a CARS spectrum by controlling each laser pulse of the emission throughout the fingerprint region. Consequently, it is theoretically able to provide stable CARS spectra to apply multivariate analysis in biological applications. The present study demonstrates that the DW-ETL CARS system provides spectra of biomedical samples in the full finger-print region, and the stability and controllability of the system are evaluated. Graphical Abstract